2000
DOI: 10.1007/s004170000185
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of ifenprodil against glutamate-induced neurotoxicity in cultured retinal neurons

Abstract: The findings suggest that ifenprodil protected the cultured retinal cells we used in this study against glutamate neurotoxicity by its inhibitory action on the polyamine modulatory site of the NMDA receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Our assays confirmed that glutamate promotes an extensive cell death (77% of total cells) after incubation for 8 h compared with control without glutamate. Interestingly, both compounds 2a and 2b protected the neurons from the glutamate effect (from 77% to 27% and 45%, respectively), values close to that detected for Ifenprodil, in this assay and in the literature (Figure 4) (29,30). No significant effect was observed when incubating these compounds with the neuron cultures without adding glutamate suggesting a safe profile.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Our assays confirmed that glutamate promotes an extensive cell death (77% of total cells) after incubation for 8 h compared with control without glutamate. Interestingly, both compounds 2a and 2b protected the neurons from the glutamate effect (from 77% to 27% and 45%, respectively), values close to that detected for Ifenprodil, in this assay and in the literature (Figure 4) (29,30). No significant effect was observed when incubating these compounds with the neuron cultures without adding glutamate suggesting a safe profile.…”
Section: Resultssupporting
confidence: 86%
“…An earlier work showed that incubation of avian retinal neurons cultures with glutamate (1 m m ) for 8 h promoted an intense cell death (28) that could be prevented by previous culture treatment with 10 μ m ifenprodil (29). Thus, triazolyl‐amidines 2a and 2b were tested for their neuroprotective potential profile by pre‐incubating the purified cultures of avian retinal neurons, prepared as described elsewhere (28), with 100 n m of the compounds solubilized in dimethyl sulfoxide (DMSO) for 48 h in the same culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…However, the neuroprotective effect promoted by ifenprodil was significantly less than that produced by MK‐801. A previous study showed that ifenprodil was equally effective as MK‐801 in protecting embryonic retinal cells in vitro exposed to glutamate (Zhang et al. 2000), suggesting that excitotoxicity was mostly mediated by polyamine binding to NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Ifenprodil is known to bind specifically to the NR2B subunit of NMDA receptors (see Supplementary Fig. S2) 28 , and its neuroprotective effect was also reported to be suppressed by spermidine 29 . In contrast, MK-801 binds to the site within the channel pore of the NR1/NR2 receptor complex (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Whether pentamidine has a neuroprotective effect in the retina and whether this effect is modified by spermidine is unknown at present. However, it was reported that spermidine suppressed the neuroprotective effect of ifenprodil in rat cultured retinal neurons 29 . The inhibitory effect of ifenprodil on MK-801 binding was also attenuated by spermidine 38 , as also seen with pentamidine.…”
Section: Discussionmentioning
confidence: 97%